Clinician perspectives on the multilevel impacts of Pediatric early warning systems (PEWS) in resource-variable hospitals - Siječić, Amela; Quesada-Stoner, Alejandra Catalina; Islam, Sayeda; Malone, Sara; Puerto-Torres, Maria F.; Cardenas Aguirre, Adolfo; Prewitt, Kim; Borborema, Maria do Céu Diniz; Ribeiro Pereira Aguiar de Paula, Andreia; Lemos de Mendonça e Fontes, Laura; Torres, Silvio Fabio; Andrade Sarmiento, Leticia Aradi; et al. (Frontiers in Oncology, 2025)
BackgroundPediatric Early Warning Systems (PEWS) are evidence-based interventions that monitor hospitalized pediatric patients to improve outcomes and prevent complications, particularly in children with cancer. However, there is limited data on how clinicians perceive the impact of PEWS on patient care across healthcare centers in resource-variable settings. Understanding clinicians’ perceptions of PEWS is crucial, as their recognition of its benefits can enhance adoption and sustainability across various healthcare settings.ObjectiveTo assess clinician perceptions of impacts following PEWS implementation across pediatric oncology centers in Latin America and Spain.MethodsWe conducted a secondary analysis of a study assessing capacity for PEWS sustainability and adaptations at resource-variable hospitals participating in a collaborative to implement PEWS. Anonymous surveys in Spanish and Portuguese were distributed to nurses, physicians, ward, and ICU clinicians using PEWS at 58 hospitals across 19 countries. The survey included one free-text question about adaptations made to PEWS. A qualitative analysis of these responses was conducted using codes developed during a previous study to describe clinician perceptions on PEWS impact. Content analysis focused on clinician perspectives on the multilevel impact of PEWS.ResultsOf 1,909 free-text responses, PEWS impact was mentioned in 48% (n=913) by clinicians at 58 participating hospitals. Participants described impacts at the level of the patient, clinician, team, and institution, and emphasized the positive impact of PEWS at their centers. PEWS was perceived as vital in facilitating timely patient care interventions, mitigating progression of critical illness, and reducing mortality for pediatric oncology patients. Clinicians also reported that PEWS made patient care easier and empowered them in their roles. Finally, PEWS was perceived to improve communication and team dynamics among multidisciplinary clinicians.ConclusionThis study adds to existing literature by describing clinician perceptions of the multilevel impacts of PEWS on hospital care for children with cancer across hospitals of diverse resource-levels, providing further evidence of how this intervention might benefit patients, clinicians, and clinical teams. These findings emphasize that understanding perspectives of clinicians who use evidence-based interventions, like PEWS is crucial to promote adoption and guide sustainability strategies to improve outcomes for children with cancer globally.